Interregnum in Providence : the fragmentation of narrative as quest in the prose fictions of Heman Melville - De Villiers, Dawid Willem,1972- (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2003.